Temel Flep Cerrahisi - Erkol, Erden Erkut; Bilirer, Ahmet; Baycar, Zikrullah; Kendir, Münür Selçuk; İsmayilzada, Majid and Akatekin, Ahmet and Işık, Cemil and Güray Evin, Şeyda and Adıgüzel, İbrahim Faruk and Acaban, M. Baver and Kabakaş, Fatih and Aksoy, Alper and Güntürk, Özgün Barış and Okyay, Mehmet Fatih and Atılgan, Numan and Gün Koplay, Tuğba and Tuluy, Yavuz and Sır, Emin and Abacı, Malik and Dağdelen, Dağhan and Yıldırım, Mehmet Emin Cem and Zuhour, Moath and Öztermeli, Ahmet and Uyar, İlker and Tutcu, Halis Kayhan and Özkan, Ömer Can and Uyanık, Orkun (Academician Publishing Book DOI Portal, 2023)
-